1989
DOI: 10.1002/1097-0142(19890701)64:1<154::aid-cncr2820640126>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial with surgery and intraperitoneal hyperthermic perfusion for peritoneal recurrence of gastrointestinal cancer

Abstract: To treat six patients with peritoneal recurrence after radical operation for gastrointestinal cancer, an intraperitoneal hyperthermic perfusion (IPHP), combined with surgical resection of recurrent tumors, intestinal bypass anastomosis, or both, was carried out. Immediately after complete resection of the intraperitoneal recurrent tumors, a 2-to 3-hour IPHP was performed under hypothermic general anesthesia at about 32"C, using a perfusate containing 10 pg/ml or 20 pg/ml of mitomycin C (MMC) warmed at the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Although thrombocytopenia and elevated serum GOT and GPT levels were observed in the CHPP group, the levels returned to within the normal range at the end of 2 weeks after CHPP. Fujimoto et al [9] observed that there was no evidence of peritoneal seeding at the time of the second intraperitoneal hyperthermic perfusion (IPHP) in 1 of 15 patients with far-advanced gastric carcinoma who had definite peritoneal seeding before the second IPHP. Fujimoto et al [10] also noted that IPHP with a closedcircuit system was a safe antitumor treatment for gastric carcinoma with peritoneal dissemination.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Although thrombocytopenia and elevated serum GOT and GPT levels were observed in the CHPP group, the levels returned to within the normal range at the end of 2 weeks after CHPP. Fujimoto et al [9] observed that there was no evidence of peritoneal seeding at the time of the second intraperitoneal hyperthermic perfusion (IPHP) in 1 of 15 patients with far-advanced gastric carcinoma who had definite peritoneal seeding before the second IPHP. Fujimoto et al [10] also noted that IPHP with a closedcircuit system was a safe antitumor treatment for gastric carcinoma with peritoneal dissemination.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Thermal probes were placed intraperitoneally and along the circuit to monitor perfusate temperature during the procedure. We performed HIIC according to either the “closed”25 or the “open” technique, the latter using a peritoneal cavity expander as reported by Fujimura et al,26 that allows the surgeon to gently but continuously manipulate the viscera to enhance drug diffusion within the abdominal cavity. Drugs were bolus‐injected into the circuit once an intraperitoneal temperature of 41.5 °C had been reached.…”
Section: Methodsmentioning
confidence: 99%
“…In the experience of Fujimoto [84], transitory hepatic dysfunction, hypoproteinemia, and thrombocytopenia occurred in all six patients undergoing CRS, and Stephens [85] found, in a series of 200 patients undergoing CRS and HIPEC with MMC, with the Coliseum technique, major complications in 27% of patients and procedure-related complications in 1.5% of patients. Some authors have reported ureteral obstructions in up to 3.9% of patients as a complication of CRS + HIPEC, proposing a prophylactic urethral stenting [86].…”
Section: Complicationsmentioning
confidence: 97%
“…Nutritional status has shown a significant prognostic value even in the study by Vashi The selection of patients for CRS plus HIPEC should be on the basis of the assessment of nutritional status and detection of ascites [53]. Nevertheless, many authors have reported the disappearance of ascites after HIPEC, although not affecting the survival [25,48,55].…”
Section: Preoperative Imagingmentioning
confidence: 99%
See 1 more Smart Citation